Enhancing IELTS Speaking Preparation: The Development of a Self-Paced Learning Model Integrating Edpuzzle and Authentic Materials - Kurnihayati Kurnihayati; Endang Siti Nurkholidah; Affan Phatthanawiwat (Qualitative and Quantitative Research Center, 2026)
High-stakes oral language assessments often present significant challenges for English as a Foreign Language (EFL) learners due to a lack of autonomous, context-rich speaking environments that support spontaneous lexical and grammatical development. To address this limitation, the present study developed and evaluated a self-paced learning model that integrates the Edpuzzle platform with authentic instructional materials specifically designed for International English Language Testing System (IELTS) Speaking test preparation. Operating within a Research and Development (R&D) design, this project applied the 4D framework across its four successive phases of define, design, develop, and disseminate to pilot the model with ten English Education majors from three Indonesian universities. Empirical data were collected and triangulated using evaluation questionnaires, semi-structured interviews, and asynchronous user engagement logs extracted directly from the platform. The findings demonstrated noticeable performance enhancements across key evaluation criteria. Quantitative assessments indicated highly favorable participant reception regarding pronunciation tasks (M = 4.8) and contextual real-world relevance (M = 4.7), whereas real-time grammatical accuracy presented a moderate ongoing challenge for learners (M = 3.0). Qualitative responses corroborated these trends, revealing that the interactive multimedia architecture reinforced learner autonomy and reflective language use, which mitigated minor technical glitches and dialectal challenges. Conceptually, this research bridges a critical gap by shifting technology-mediated authentic learning out of traditional teacher-centered classrooms into a fully self-directed environment. Practically, it offers an accessible, scalable pedagogical framework for autonomous test preparation, thereby advancing multimedia instructional design within global EFL frameworks.